UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK DENGAN PEMBELAJARAN BERBASIS MASALAH BERBANTUAN GEOGEBRA - Ratna Kartika Sari Ratna Kartika Sari (Eksponen, 2023)
: This study intends to enhance mathematical problem-solving abilities through a problem-based learning model supplemented by GeoGebra in class X students of SMK Negeri 4 Semarang in 2022/2023. The subjects of this class action research were 36 students in class X TE 2 of SMK Negeri 4 Semarang for the 2022/2023 academic year as the subjects receiving the action. Techniques for collecting data include testing, observing, and documenting. This classroom action research is conducted in three cycles, each of which includes the steps of planning, acting, observing, and reflecting. The results of this study point to enhancing the mathematical problem-solving abilities of class X students of SMK Negeri 4 Semarang through problem-based learning models supplemented by GeoGebra. This is evident from the average value of mathematical problem-solving abilities which has increased, was 64.86 in the 1st cycle, 79.25 in the 2nd cycle, and 87.22 in the 3rd cycle. In addition, classical student learning completeness was 44.44% in the first cycle, 77.78% in the second cycle, and 91.67% in the third cycle.